2017
DOI: 10.1590/1413-785220172504156564
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Functional Capacity in Individuals With and Without Chronic Lower Back Pain

Abstract: Objective: The objective of this study was to analyze the functional status of adult and older adult individuals with lower back pain . Methods: Eighty-three individuals were recruited, 42 older adults (20 with lower back pain and 22 control group) and 41 younger adults (21 with lower back pain and 20 control group). Functional capacity was assessed using the following tests: Timed Up and Go (TUG), Five Times Sit-to-Stand (FTSTS), six-minute walking test (SMWT), and sitting-rising test (SRT) . Results: In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The performance of the gait speed test, 6MWT, handgrip strength, and chair-stands test has not been evaluated in women with endometriosis in previous studies. However, similar to our results, worse physical performance has been reported in other populations with a diagnosis of untreated chronic pain ( Rodrigues et al, 2017 ). Chronic pain can induce fear and movement blocking behaviors, which often results in low physical performance ( Luque-Suarez, Martinez-Calderon & Falla, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…The performance of the gait speed test, 6MWT, handgrip strength, and chair-stands test has not been evaluated in women with endometriosis in previous studies. However, similar to our results, worse physical performance has been reported in other populations with a diagnosis of untreated chronic pain ( Rodrigues et al, 2017 ). Chronic pain can induce fear and movement blocking behaviors, which often results in low physical performance ( Luque-Suarez, Martinez-Calderon & Falla, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…For the objective higher-order theme, there were three sub-themes with 17 core categories: simple capacities, combined capacities, and complex capacities. Most researchers adopted the gait speed measures [ 24 , 30 , 35 , 38 , 39 , 40 , 41 ] to assess older adults’ simple capacities. The timed up and go test [ 31 , 42 , 43 ], sit-to-stand test [ 32 , 44 ], stabilometer and posture meter platforms [ 40 , 45 ] and the one-repetition maximum test [ 46 , 47 ] were also implemented in more than one study.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, simple capacities such as mobility, strength, aerobic fitness, flexibility, and balance were assessed through simple but effective instruments. The gait speed measures [ 24 , 30 , 35 , 38 , 39 , 40 , 41 ] were embraced by most researchers for their function serving as a core indicator of health and function in ageing and disease. But this was often simply introduced in clinical settings to monitor and evaluate changes.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should consider monitoring the perceived level of effort and discomfort during the execution of the tasks to provide more information regarding the underlying mechanisms of the observed differences related to the CRT and TUG. Notably, Rodrigues et al reported no statistically significant differences in the CRT results between healthy and symptomatic patients, who were matched by age, gender and by the amount of weekly physical activity [ 41 ]. According to the average body mass of compared groups in our study, we could speculate that the LBP patients were physically less active than the CG, but we cannot know whether this phenomenon was established before the onset of LBP, nor do we know whether that was the cause for lower performance in the CRT and TUG.…”
Section: Discussionmentioning
confidence: 99%